Analisis pengaruh tarif pajak, kepercayaan, pengetahuan dan kesadaran wajib pjak terhadap kepatuhan pelaku UMKM dalam membayar pajak - Norman Duma Sitinjak; Ananda Yosi Puguh (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2022)
This research aims to test whether tax rates, taxpayer confidence, taxpayer knowledge and taxpayer awareness can affect the compliance of MSMEs in paying taxes. This research focuses on MSMEs in Malang city area. The type of research the authors use is quantitative-based research. The data source used is primary data with data collection techniques using questionnaires distributed online using purposive sampling techniques with criteria that MSMEs must have NPWP and have MSME revenue Rp 300,000,000 in a year. Data analysis techniques use multiple linear regression analysis using the help of the SPSS 25 program. The results of the study showed that the variable Tax Rate (X1), and Taxpayer Knowledge (X3) had a simultaneous and significant effect on tax compliance, while the Variables of Taxpayer Awareness (X2) and Taxpayer Trust (X4) had a simultaneous effect but did not significantly affect the compliance of MSME taxpayers